2021
DOI: 10.3390/ijms23010428
|View full text |Cite
|
Sign up to set email alerts
|

YB-1 Phosphorylation at Serine 209 Inhibits Its Nuclear Translocation

Abstract: YB-1 is a multifunctional DNA- and RNA-binding protein involved in cell proliferation, differentiation, and migration. YB-1 is a predominantly cytoplasmic protein that is transported to the nucleus in certain conditions, including DNA-damaging stress, transcription inhibition, and viral infection. In tumors, YB-1 nuclear localization correlates with high aggressiveness, multidrug resistance, and a poor prognosis. It is known that posttranslational modifications can regulate the nuclear translocation of YB-1. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…In human breast and ovarian cancer cells, it has been reported that the S102 of YB-1 is phosphorylated by PI3K/Akt pathway, and this phosphorylation in turn induces nuclear translocation of YB-1 [22, 54] as well as its dissociation from the capped mRNAs, therefore increasing their translation [30]. Interestingly, in contrast to S102, the phosphorylation at S209 also by Akt inhibits YB-1 nuclear translocation [55].…”
Section: Discussionmentioning
confidence: 99%
“…In human breast and ovarian cancer cells, it has been reported that the S102 of YB-1 is phosphorylated by PI3K/Akt pathway, and this phosphorylation in turn induces nuclear translocation of YB-1 [22, 54] as well as its dissociation from the capped mRNAs, therefore increasing their translation [30]. Interestingly, in contrast to S102, the phosphorylation at S209 also by Akt inhibits YB-1 nuclear translocation [55].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation at S102 in the CSD region is the most widely reported post-translational modification of YB-1 [ 104 ]. In addition, YB-1 phosphorylation sites contain S30/34 [ 154 ], S176 [ 155 , 156 ], S165 [ 157 ], Y162 [ 158 , 159 , 160 ], S209 [ 161 ], and Y188 [ 162 ]. First, AKT [ 161 ], ERK [ 163 ], and RSK1/2 [ 106 ] were identified as kinases that directly phosphorylate YB-1.…”
Section: Upstream Regulation Of Yb-1mentioning
confidence: 99%
“…In addition, YB-1 phosphorylation sites contain S30/34 [ 154 ], S176 [ 155 , 156 ], S165 [ 157 ], Y162 [ 158 , 159 , 160 ], S209 [ 161 ], and Y188 [ 162 ]. First, AKT [ 161 ], ERK [ 163 ], and RSK1/2 [ 106 ] were identified as kinases that directly phosphorylate YB-1. Similarly, a number of factors that indirectly promote YB-1 phosphorylation were identified.…”
Section: Upstream Regulation Of Yb-1mentioning
confidence: 99%
“…4 D, E ) 41 , 42 . It remains to be tested whether other phosphorylations of YBX1 such as phospho-S209 43 affect the YBX1 function in tumour growth and invasion 44 , and in PIK3CA mutant HNC as seen in JAK2 mutant hematopoietic cancers 45 . In the absence of PI3K signalling, YBX1 binds to mRNAs of p-EMT markers in the cytoplasm 20 .…”
Section: Discussionmentioning
confidence: 99%